Proceedings of Tourism Development Centre International Conference. Sustainable Tourism Development in Disaster Prone Destinations - Ma'ruf (De Gruyter, 2020)
This proceeding contains peer-reviewed papers from the Tourism Development Centre International Conference (TDCIC), October 1st, 2019, in Bukittinggi, West Sumatra, Indonesia. This conference focused on current issues of sustainable tourism in a disaster prone destination with the focused on marine and coastal tourism to discuss and disseminate research findings, elaborate concepts and methods, share idea and experiences among participants. Papers presented in the conference covered a wide range of topics: Tourism Safety and security, Sustainable and Ecotourism, Tourism and Climate Change, Community Based Tourism, Marine and Coastal Tourism, Tourism Management, Traveller Behavior, Tourist Experience, Sharing Economic in Tourism, Robotic and AI in Tourism, Halal Tourism, Local Wisdom in Tourism and International and Domestic Law in Tourism. This International Academic Conference aims to facilitate discourses and develop innovative and critical thinking around Sustainable Tourism in Disaster Prone Destinations issues. This conference invited experts, practitioners, and stakeholders in tourism from ASIAN countries, Australia and South Korea. The topic of papers for this conference covers all aspects of tourism. The conference has two programs: (1) International Academic Conference where a number of internationally acknowledged experts delivered speeches as keynote and invited speakers in the plenary session. The event then continued with parallel panels discussing specific areas of sustainable tourism, safety, and security tourism with presenters selected from the call for papers. Based on these presentations, participants were further offered post-conference publication opportunities in a range of forms such as international journals, national journals, conference proceeding with Scopus indexed, and edited books. (2) Academic Professional Gathering. This program was aimed at exposing The Tourism Development Center - Universitas Andalas activities, achieveme